PEMBERDAYAAN TOUR GUIDE EKOTURISME DI KAWASAN CAGAR BUDAYA DANAU TAMBLINGAN-BATUKARU BALI - I Nyoman Wardi (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractTraining Ecotourism Tour Guide Batukaru Heritage Region-Lake Tamblingan performed atMunduk Buleleng on 1 until 7 September 2012. The community service was held in SD 3hall Tamblingan and the meeting was attended by 20 participants from organisation guide(OBB) including the head of OBB (Organisasi Bangkit Bersama). The aims of this trainingto enhance the knowledge and skills as a tracking tour guide in Batukaru-Tamblingan.Training is also intended to provide a briefing on the knowledge ecosystem of lakes, forestand about the history and function of the cultural heritage in the region Batukaru-Tamblingan which now has been declared by UNESCO as a World Cultural Landscape inBali.As a local tour guide, which is still weak foreign language skills, age, and education levelof the participants is quite heterogeneous effect on the rate of absorption ability and spirittraining. Ecotourism tour guide training is expected to re-integrate the social cohesionand sustainable society in harmony.Recognizing the heterogenity of the condition of the trainee, techniques and methods ofpresentation of training materials, must be adapted to the conditions so that the materialcan be absorbed optimal. The first material was delivered in a lecture and presented byusing the Microsoft Power Point program and discussion to increase participants intereston the topic. Second, the practice of direct methods on objects that exist in the empiricalTamblingan Munduk Village. The practice of tour guide in the field for two days with shorttrack and medium tract.Based on the evaluation performed the training process, and from the impressions andmessages conveyed by the trainees at the time of closing, was satisfied and happy training.A participants gave very enthusiastic responses and are expected to continue to be thequality of human resources and OBB members of the community can be improved.